Poultry Farms and Their Waste Disposal Techniques in Virudhunagar District, India: Issues and Challenges - Bhastina, J. Jasmine; Kumar, M.J. Senthil; P.Arumugapandi; M.Ishwarya; Sathana, T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The poultry industry in Virudhunagar district, Tamil Nadu, significantly contributes to the region’s economy and food security. However, the rapid growth of poultry farming has resulted in considerable waste management issues, leading to environmental harm, contamination of groundwater, and public health concerns. This study examines the waste disposal methods utilized by poultry farms in Virudhunagar, with a particular emphasis on sustainable approaches like composting, anaerobic digestion, and organic fertilizer production. Using a descriptive research design and a mixed-methods approach, the study surveyed 75 poultry farmers to assess their waste disposal practices, awareness levels, and challenges faced. The findings suggest that landfilling and open-area disposal continue to be the primary waste management practices, with minimal adoption of more sustainable alternatives. The study identifies several barriers to the adoption of environmentally friendly practices, including financial limitations, lack of technical knowledge, and insufficient resources. The research emphasizes the urgent need for increased awareness, financial assistance, and technical training to promote sustainable waste management in the poultry sector of Virudhunagar.